Key elements to enable systemic innovation in construction firms - Duarte, Carolina Mendonça de Moraes; Picchi, Flávio Augusto (Ambiente Construído, 2021)
The construction industry is generally known to be resistive to change and reluctant to embrace new technologies. Innovation, which might be described as the successful exploitation of new ideas, is usually seen as the key to unlocking the industry’s potential. Although there is no doubt that some progress has been made, construction innovation still occurs in a random manner, not as a systemic and managed process. Regardless of the growing number of studies on construction innovation management, there is still a lack of research that identify, compile, classify, and summarize the innovation enablers in construction. Thus, based on a Systematic Literature Review (SLR), this paper aims to provide a holistic understanding of the key elements that enable systemic innovation in construction from a firm-level perspective. The review incorporated data from 38 articles to establish a set of 15 enablers of innovation in construction firms, such as innovation culture, external collaboration (open innovation), knowledge management, and upper management support. The enablers were classified into five different aspects of innovation management: strategic, organizational, human, processual, and financial. The review also sought to identify practices, routines, methods, or tools that can be adopted to increase innovation activity in construction firms.